Beyond the scholarly discourse - several ways to show the hidden curriculum - Daniela Jeder; Daniela Jeder (Association of Social and Educational Innovation, 2017)
The paper aims to capture a series of teaching speech coordinates, focusing on dimensions less obvious or visible, expression of a covered / hidden curriculum with a marked impact on the formation. The awareness of these implications provide a fuller picture of the dynamics of the educational space and supports the development of ethical and professional conscience, so necessary to trainers.